Synthesis of mesoporous TiO2/gamma-Al2O3 composite granules with different sol composition and calcination temperature - Choi, Junseo; Kim, Jinsoo; Yoo, Kye Sang; Lee, Tai Gyu (ELSEVIER SCIENCE SA, 2008)
Mesoporous TiO2/gamma-Al2O3 composite granules were prepared by combining sol-gel method and oil-drop method. After calcination at 450 degrees C, the composite granules showed anatase and gamma-Al2O3 phases with the specific surface area of 240-310 m(2)/g. The phase composition and pore structure of the granules can be controlled by calcination temperature and the mixing ratio of bochmite sol and titania sol. The product granules can be used as a photocatalyst or adsorbent in moving or fluidized bed reactors. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ALUMINA GRANULES; SURFACE-AREA; CERAMICS; TITANIA; POWDERS